2007
DOI: 10.1007/s00213-007-0756-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of the d- and l- isomers of amphetamine on pharmacological MRI BOLD contrast in the rat

Abstract: Rationale The D-and L-amphetamine sulphate isomers are used in the formulation of Adderall XR®, which is effective in the treatment of attention-deficit hyperactivity disorder (ADHD). The effects of these isomers on brain activity has not been examined using neuroimaging. Objectives This study determines the pharmacological magnetic resonance imaging blood-oxygenation-level-dependent (BOLD) response in rat brain regions after administration of each isomer. Materials and methods Rats were individually placed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 104 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…Nevertheless, anaesthesia in rodent MRI studies is sometime necessary, especially when scanning duration takes longer than 2 h. Inhalation anaesthetics are widely used in phMRI studies (Abo et al 2003;Hewitt et al 2005;Shoaib et al 2004;Sicard et al 2003;Sicard and Duong 2005). Isoflurane is widely used because it produces stable anaesthesia over a prolonged period of time, with minimal physiological alterations (Easton et al 2007a;Easton et al 2007b). In our present study, we cannot discard the possibility that the observed BOLD profiles are due to combined effects of both MPH plus the anaesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, anaesthesia in rodent MRI studies is sometime necessary, especially when scanning duration takes longer than 2 h. Inhalation anaesthetics are widely used in phMRI studies (Abo et al 2003;Hewitt et al 2005;Shoaib et al 2004;Sicard et al 2003;Sicard and Duong 2005). Isoflurane is widely used because it produces stable anaesthesia over a prolonged period of time, with minimal physiological alterations (Easton et al 2007a;Easton et al 2007b). In our present study, we cannot discard the possibility that the observed BOLD profiles are due to combined effects of both MPH plus the anaesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have used SPM techniques in rats with different imaging modalities: autoradiographic iodoantipyrine [30][31][32][33][34], fMRI [35][36][37][38][39][40], and FDG-PET [20,41,42]. Two PET studies used a standardization according to a custom digital template matched to a highresolution microMRI image in Paxinos orientation [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib inhibits tumor cell proliferation and tumor cell vacularisation through activating the receptor tyrosine kinase signaling RAS/RAF/MEK/ERK cascade pathway . Sorafenib is often obtained by over 4 steps of chemical synthesis, and the intermediates and side products including the positional pattern of substituents are usually the main potential impurities which may influence quality, efficacy, and safety of final products . The international conference on harmonization of technical requirements for registration of pharmaceuticals of human use (ICH) recommends that the amounts of impurities are limited to less than 0.1% .…”
Section: Introductionmentioning
confidence: 99%